1999
DOI: 10.1080/713755856
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Processes Underlying Observational Learning of Motor Skills

Abstract: There is evidence indicating that an individual can learn a motor skill by observing a model practising it. In the present study we wanted to determine whether observation would permit one to learn the relative timing pattern required to perform a new motor skill. Also, we wanted to determine the joint effects of observation and of physical practice on the learning of that relative timing pattern. Finally, we were interested in finding whether there was an optimal type of model, advanced or beginner, which wou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
37
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(54 citation statements)
references
References 28 publications
14
37
0
3
Order By: Relevance
“…Since the primary guidance provided by the machine is the control of moving speed, the effectiveness and usefulness of providing external help was strongly supported by this result. This finding is consistent with previous research by Blandin, et al (1999), and Black and Wright (2000) that pointed out physical practice had more positive impact on controlling time than observational practice. Moreover, in a study on haptic training by Feygin, et al(2002) it was also found that timing accuracy was dominated by haptic training while position and shape accuracy were dominated by visual training.…”
Section: Moving Speedsupporting
confidence: 83%
“…Since the primary guidance provided by the machine is the control of moving speed, the effectiveness and usefulness of providing external help was strongly supported by this result. This finding is consistent with previous research by Blandin, et al (1999), and Black and Wright (2000) that pointed out physical practice had more positive impact on controlling time than observational practice. Moreover, in a study on haptic training by Feygin, et al(2002) it was also found that timing accuracy was dominated by haptic training while position and shape accuracy were dominated by visual training.…”
Section: Moving Speedsupporting
confidence: 83%
“…Simultaneamente ao estudo da demonstração na abordagem da ação, vários estudos [43][44][45] têm investigado esse mesmo tipo de instrução na abordagem motora. Eles têm pesquisado sobre a natureza da informação e sobre a aquisição dos mecanismos de detecção e correção de erros por meio da observação do modelo.…”
Section: Contribuições Da Abordagem Motora E Da Açãounclassified
“…In addition, they have been successfully used for teaching metacognitive skills such as self-regulation (e.g., Kitsantas et al 2000;Zimmerman and Kitsantas 2002) or (self-) assessment (Van Gog et al, in press). In contrast to worked examples, modeling examples are also highly suitable and are widely used to teach (psycho)motor skills (see, e.g., Blandin et al 1999;Wright et al 1997). Research on the mirror neuron system has provided important insights into the underlying mechanisms of observational learning of motor skills, by showing that the same neural circuits that are involved in executing a motor action oneself, also respond to observing someone else executing that action (for a review, see Rizzolatti and Craighero 2004).…”
Section: For What Kinds Of Tasks Is Example-based Learning Effective?mentioning
confidence: 99%